"Between a Rock and a Hard Place": Planning Reform, Localism and the Role of the Planning Inspectorate in England. (15th March 2018) - Boddy, Martin; Hickman, Hannah
Abstract: Like many European countries, England saw the establishment in the late 1990s and early twenty-first century of regional-scale spatial planning. Radical reform of English planning following the Localism Act 2011 however saw the whole intermediate tier of regional planning stripped out of the national planning system along with detailed guidance and top-down targets for house-building at a local level. This had a major impact on the Planning Inspectorate, the agency responsible on behalf of government for approving local development plans. Reform left the Inspectorate fully exposed to the tensions and contradictions between top-down policy and local autonomy inherent under the new planning framework. Focussing on future levels of housing development, a key responsibility of local councils under the new framework, we examine the implications of reform for the Planning Inspectorate in practice. We draw on approaches to localism and planning theory, in particular the idea of 'conditional localism', in order to situate and understand these changes. The study was based on interviews with elite respondents in or close to the Planning Inspectorate together with documentary sources. Lack of previous work on the Inspectorate, coupled with their key role in the national planning system, reinforced by recent reforms, emphasises the significance of the study. The importance of such 'land-use tribunals' internationally, points to the study's wider relevance. It provides, as well, a study of planning reform with relevance in a wider European context and suggests how recent contributions to the localism debate can help make sense of these changes.